Nurse Assisted Distraction Strategies (NADS) on Postoperative Pain Experience among Children Undergoing Surgery: A Study Protocol (Medico Legal Update, 2020)
Purpose: To evaluate the efficacy of nurse assisted distraction strategies on postoperative pain, parent paincatastrophizing, mother and child anxiety and physiological parameters.Method: The present study included a total of 160 mother-child dyads (2-7 years) inpatient to paediatricsurgical unit. The study participants are randomized into intervention and control group. The interventiongroup will receive age appropriate NADS along with the standard care for three postoperative days and thecontrol group will receive only standard care. The participants will be followed from day of admission topostoperative day 3.Results: NADS will be delivered for three postoperative days to the children in the postoperative unit.Children received intervention had shown improvement in the postoperative pain and anxiety in these threepostoperative days.Conclusion: The findings of the study will empower nurses and health care professionals to practicedistraction strategies in the postoperative unit which will decrease postoperative pain, anxiety and reducesthe dosage of analgesics among children